GAMBARAN POLA KONSUMSI DAN STATUS GIZI BADUTA (BAYI 6-24 BULAN) YANG TELAH MENDAPATKAN MAKANAN TAMBAHAN TABURIA DI KELURAHAN KEMENANGAN TANI KECAMATAN MEDAN TUNTUNGAN TAHUN 2012 - Mona Sylvia Junita; Albiner Siagian; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Taburia means supplemental food of multivitamin and multimineral to fulfill nutrient needs and the growth for the babies aged 6-24 months. Taburia is as the expansion of local product of micronutrient powder (MNP) and as the strategy to overcome the anemia as the effect of iron deficiency and other micro nutrient deficiencies. The objective of this research was to know the description of consumption pattern and nutrient status of the babies aged 6-24 months getting Taburia in Kemenangan Tani area, Medan Tuntungan, Medan City in 2012. This research was quantitative descriptive with Cross sectional design. The results of research showed that consumption pattern of the babies aged 6-24 months based on the category of food menu was categorized good for 67,7% and consumption pattern of the babies aged 6-24 months based on the category of eating frequency was categorized good for 53,2%, whereas based on the weight per age was categorized normal for 57,6%, nutritional status based on height per age was categorized normal for 68,1% and nutritional status based on weight per height was categorized normal for 73,0%. Taburia administration program may enhance nutritional status of two years old of the babies into normal. Hence, it is expected that Health Department should continue Taburia administration program since it is proved that it may enhance nutritional status of two years old of the babies in Kemenangan Tani area, Medan Tuntungan and also it is expected that Primary Health Center is more active in giving the socialization of information and counseling about good consumption pattern of the baby and Taburia administration.